Case of primary diffuse large B-cell lymphoma of lacrimal sac in a Japanese patient - Fusae Kajita (Dove Medical Press, 2010)
Fusae Kajita1, Toshiyuki Oshitari1, Jiro Yotsukura1, Kaoru Asanagi1, Takayuki Baba1, Takashi Kishimoto2, Shuichi Yamamoto11Department of Ophthalmology and Visual Science, 2Department of Molecular Pathology, Chiba University Graduate School of Medicine, Chiba, JapanAbstract: The purpose of this study was to determine the characteristics of primary diffuse large B-cell lymphoma (DLBCL) of the lacrimal sac. A 77-year-old man had epiphora of the right eye for three years. After visiting five clinics and hospitals, he was referred to our hospital, and the preoperative magnetic resonance imaging findings suggested a lacrimal sac mass. Dacryocysteography showed an obstruction of the right nasolacrimal duct, so we performed dacryocystectomy. After a histopathologic examination of the specimen, the patient was diagnosed with a DLBCL. Positron emission tomography scanning excluded metastases, and the final diagnosis was made of a primary DLBCL of the right lacrimal sac. He underwent radiotherapy with 30.6 Gray in total to the right lacrimal sac. After radiotherapy, no recurrence has been observed anywhere in his body for one year. Although a malignant lymphoma of the lacrimal sac is rare, clinicians should consider a primary malignant lymphoma in the differential diagnosis in patients with chronic dacryocystitis.Keywords: lacrimal sac, diffuse large B-cell lymphoma, radiotherapy, dacryocystectomy, Japanese